The Levels of Vitamine A in Laryngeal Carcinoma - Gök, Üzeyir; Tazegül, Ayca (Fırat University, 2005)
Objectives: To investigate the level of vitamin A which cause the inhibition of the cell proliferation and induction of the cell differantation in the carcinoma of the larynx. Materials and Methods: This study included the 29 patients who had the carcinoma of the larynx. Mean age of the patients was 58,7±7,4. All of the patients were male and none of them were using vitamins. Levels of Vitamin A were evaluated in all patients. Findings were compared with control group that included 32 subjects. Results: Asignificant decrease was seen in the levels of vitamin A in patients with carcinoma of the larynx when compared with the levels of vitamin A in control group(p

Amaç: Hücre proliferasyonunun inhibisyonu ve hücresel diferansiyasyon indüksiyonuna neden olan A Vitamini'nin larenks karsinomunda düzeyini araştırmak. Gereç ve Yöntem: Çalışmaya 29 larenks epidermoid karsinomlu hasta alındı. Yaş ortalaması 58,7±7,4 idi. Hastaların tümü erkek ve daha önceden vitamin kullanım hikayesi yoktu. Tüm hastaların A vitamini düzeyleri ölçüldü ve 32 kişilik kontrol grubu ile karşılaştırıldı. Bulgular: Hasta grubunun Vitamin A düzeyleri kontrol grubu ile karşılaştırıldığında hasta grubun Vitamin A düzeylerinde anlamlı düzeyde düşük olduğu (p
Larenks Epidermoid Kanserinde Vitamin A Düzeyi